FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM BERINVESTASI DI PASAR MODAL: Studi Kasus pada Mahasiswa di Medan - Merry Moy Mita; Supriadi Siagian (Universitas Methodist Indonesia, 2021)
Capital market is an economic activity that trades securities according to investment, namely stocks, bonds and mutual funds. The capital market was developed in order to accommodate the needs of people in Indonesia who wish to invest in capital market products. The purpose of this study was to determine the factors that influence the interest of Medan students in investing in the capital market. The sample in this study is Medan students who want to invest and try to invest in the capital market, with a sample of 122 students with the sampling method used is purposive sampling with the Slovin formula. The dependent variable in this study is interest and the independent variables in this study are minimum investment capital, perceived return, perceived risk, investment benefits and motivation. The research method used is a quantitative method with primary data obtained from questionnaire data measured by a Likert scale. The data analysis technique used in this research is multiple linear regression analysis. The research data was collected using a questionnaire which was then processed using the SPSS 21.0 program. The results obtained from this study are the perceived investment benefits variable (X1) and perceived return (X2) have less effect on student interest in investing, while the Self efficacy variable (X3) and knowledge of investment (X4) affect the interest of field students in investing in the capital market.